Neutrophil Count, Intracranial Atherosclerotic Stenosis, and Prognosis of Ischemic Stroke After Endovascular Treatment: A Mediation Analysis - Li, Tingting; Chen, Zhonglun; Zhu, Xuyin; Tang, Xianbiao; Pan, Song; Gong, Fan; Xu, Leyi; Wang, Mingzhe; Zhang, Hongzhi; Guo, Yongmei; Zhang, Jingsi; Qin, Baofeng; et al. (Frontiers in Neurology, 2020)
Background and Purpose: Data on the relationship among neutrophil count, intracranial atherosclerotic stenosis (ICAS), and functional outcomes after endovascular thrombectomy (EVT) for ischemic stroke patients remains unclear. We aimed to evaluate the association between neutrophil count and prognosis of EVT patients and to determine whether the association was mediated by ICAS. Methods: We retrospectively analyzed consecutive patients who underwent EVT at 2 comprehensive stroke centers between June 2016 and December 2019. A remaining stenosis >70%, or a lesser degree of stenosis with a tendency toward re-occlusion or flow impairment during the procedure, was classified as ICAS. Poor outcome was defined as a 90-day modified Rankin Scale score of 3 to 6. Results: Of 221 patients (mean age, 65.9 years; males, 61.1%) included in this study, 81 (36.3%) had ICAS, and 120 (54.3%) experienced poor outcome at 90 days, respectively. In the multivariate adjustment for potential confounders, neutrophil count (odds ratio [OR], 1.19; 95% confidence interval [CI], 1.04–1.36; P = 0.012) and presence of ICAS (OR, 2.65; 95CI%, 1.28–5.45; P = 0.008) were risk factors of poor outcomes. Furthermore, mediation analysis indicated that total ICAS mediated the association between increased neutrophil count and worse functional outcome after EVT (the regression coefficient was changed by 11.7% for poor outcome, and 17.1% for modified Rankin Scale score, respectively). Conclusions: Our study demonstrated that a higher neutrophil count might increase the risk of poor outcome among ischemic stroke underwent EVT, which was partially mediated by ICAS.